A Bayesian network meta‐analysis of orthopaedic treatment in Class III malocclusion: Maxillary protraction with skeletal anchorage or a rapid maxillary expander. (15th September 2019) - Wu, Zuping; Zhang, Xin; Li, Zixuan; Liu, Yuyao; Jin, Hairu; Chen, Qian; Guo, Jie
Abstract: To evaluate and compare the effectiveness of orthopaedic treatment for Class III malocclusions using skeletal anchorage or a rapid maxillary expander for maxillary protraction. Electronic databases, including PubMed, EMBASE, Cochrane Library and Web of Science, were searched for randomized controlled trials (RCTs) and non‐randomized clinical trials (CCTs) for orthopaedic treatment of Class III malocclusions. Five interventions were studied: a facemask with a maxillary temporary anchorage device (MTAD), a bone‐anchored rapid maxillary expansion (BARME), a rapid maxillary expansion (RME), an alternate rapid maxillary expansion and contraction (Alt‐RAMEC), and a bone‐anchored intermaxillary traction (BAIMT). Eight outcomes (SNA, SNB, ANB, overjet, SN‐GoGn, ANS‐Me, IMPA (L1‐MP), and U1‐PP) were statistically polled. We conducted network meta‐analysis using R statistical software with the GeMTC package. Twenty‐five studies met the inclusion criteria. Compared with the RME group, the Alt‐RAMEC group (mean difference (MD): 1.3; 95% credibility interval (CrI): 0.26, 2.3) and MTAD group (MD: 0.85; 95% CrI: 0.065, 1.6) showed a better effect on ANB in CCTs. Regarding the vertical relationship, the BAIMT group (MD: −2.2; 95% CrI: −5.2, 0.73) showed a smaller effect regarding increasing the vertical dimension of ANS‐Me. The RME, MTAD and Alt‐RAMEC group showed a higher ability to decrease the angle of L1‐MP. The Alt‐RAMEC and MTAD protocol have a higher possibility to obtain a skeletal and tooth effect in sagittal relationships. The BAIMT protocol can acquire a better skeletal effect in sagittal relationships with less vertical and dental changes. More well‐designed RCTs are needed to ensure that the conclusion is reliable.